Research on vibration and noise of amorphous alloy 3D wound core transformer considering magnetostrictive effect - Han, Jianwei; Yao, Xinglong; Wang, Xiaohui; Yan, Yunfei; Zhu, Endong; He, Zhi; Zhang, Lisong; Yu, Zhanyang; Zhan, Mengyu (Frontiers in Materials, 2025)
The significant magnetostrictive effect of amorphous alloy leads to severe vibration of iron core and debris shedding, which limits the wide application of amorphous alloy materials in transformer field. Therefore, the vibration characteristics of amorphous alloy coil core transformer are analyzed in this paper. Firstly, a mathematical model for predicting the magnetostrictive characteristics of the core material is constructed, and the magnetostrictive characteristics of amorphous alloy core is accurately measured with the help of a high-precision laser tester. This model can accurately reflect the vibration characteristics under magnetostrictive effect. Secondly, the vibration and noise characteristics of amorphous single frame coil core are analyzed. An amorphous alloy transformer with a rated capacity of 50 kVA was used as the experimental object to carry out a comprehensive experimental test. The key indicators such as vibration amplitude, frequency distribution and noise spectrum of the core were tested. The results show that the experimental and simulation data are highly consistent, which strongly confirms the accuracy and reliability of the simulation model. Finally, the influence mechanism of clamping force on vibration characteristics of amorphous alloy core is considered, and the relationship between clamping force and vibration characteristics is revealed.